Development of Thermoresponsive Hydrogels with Mucoadhesion Properties Loaded with Metronidazole Gel-Flakes for Improved Bacterial Vaginosis Treatment - Andi Dian Permana; Rangga Meidianto Asri; Muhammad Nur Amir; Achmad Himawan; Andi Arjuna; Nana Juniarti; Rifka Nurul Utami; Sandra Aulia Mardikasari (MDPI AG, 2023)
Bacterial vaginosis is an infectious disease that has significantly affected women's health. Metronidazole has been widely used as a drug for treating bacterial vaginosis. Nevertheless, the currently available therapies have been found to be inefficient and inconvenient. Here, we developed the combination approach of gel flake and thermoresponsive hydrogel systems. The gel flakes were prepared using gellan gum and chitosan, showing that the incorporation of metronidazole was able to provide a sustained release pattern for 24 h with an entrapment efficiency of >90%. Moreover, the gel flakes were incorporated into Pluronics-based thermoresponsive hydrogel using the combination of Pluronic F127 and F68. The hydrogels were found to exhibit the desired thermoresponsive properties, showing sol-gel transition at vaginal temperature. Following the addition of sodium alginate as a mucoadhesive agent, the hydrogel was retained in the vaginal tissue for more than 8 h, with more than 5 mg of metronidazole retained in the ex vivo evaluation. Finally, using the bacterial vaginosis infection model in rats, this approach could decrease the viability of Escherichia coli and Staphylococcus aureus with reduction percentages of more than 95% after 3 days of treatment, with the healing ability similar to normal vaginal tissue. In conclusion, this study offers an effective approach for the treatment of bacterial vaginosis.